An investigation of metastatic markers in models of paediatric medulloblastoma - Nasir, Aishah (2017)
Introduction Medulloblastoma is an aggressive malignant neuro-ectodermal tumour of the cerebellum which accounts for 15-20% of childhood central nervous system tumours and frequently disseminates to the leptomeningeal spaces of the brain and spinal cord. Patients with disseminated disease respond poorly to post-surgical multimodal treatment which is thought to be explained by the intrinsic drug-resistant nature of these tumours. Here, we hypothesized that cells gain migratory and invasive capabilities by undergoing an Epithelial-Mesenchymal Transition (EMT)-like process whereby cells alter phenotypically and acquire stem cell-like properties during tumour dissemination. In this study, metastatic genes were identified and tested using 3D in vitro model systems which incorporated important components of the extracellular matrix. Using these markers, evidence for an EMT-like process and the role of the multi-drug transporter, ABCB1, was investigated in metastatic medulloblastomas. Small molecule inhibitors were also used to investigate whether metastatic processes could be targeted and drug resistance mechanisms could be circumvented in both in vitro and/or in vivo settings.